The factors that contribute to customer acceptance towards takaful product in Malaysia/ Mukhlis Muhamad - Muhamad, Mukhlis
Islam advances the demonstration of taking safety oriented measures or ikhtiar" against any dangers. Takaful protection is a kind of Islamic managing an account that are developed in Malaysia around 1984. It is a protection item which depends on Shariah consistence. Takaful holds an alternate idea from routine protection which is rejected by the Shariah because of components of instability (gharar), interest (riba) and betting (maysir). Along these lines, Takaful is viewed as a choices for the Muslim in Malaysia who look for the securities however tail every one of the controls that had been expressed in Islam. Takaful is as yet encountering moderate pace of development contrasted with routine protection. It is strange to know that the Islamic product still cannot survive even though operating in a country that are Muslim majority. This study was conducted to know the factors that contributes to customer acceptance towards Takaful product in Malaysia.